Effect of Gynura procumbens (Sambung Nyawa) on Sheep Performance, Health Status, and Methane Emission: Efek Gynura procumbens (Sambung Nyawa) pada Performa, Status Kesehatan dan Emisi Gas Metana pada Domba (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2024)
Gynura procumbens (Sambung nyawa) has been widely used as a herbal medicine since it is rich in bioactive compounds. Moreover, Gynura procumbens also has become a potential plant that control parasitic nematode infection.  The research aimed to investigate the effect of G. procumbens on sheep performance, health status, and methane production. A total of twelve six-month-old lambs (ABW 11.27 ± 2.19 kg) were categorized based on live weight and fed one of feed treatments: wild grasses (40%) and concentrate (60%) (control/P0), P0 + 5% G. procumbens (P1), and P0 + 10% G. procumbens (P2). Feed intake, parasitic infection, and physiological status were measured weekly. G. procumbens at 5% level showed normal respiration rate, but the respiration and heart rates of lambs were abnormal. The 10% G. procumbens increased daily weight gain. G. procumbens addition up to 10% reduced the number of Strongyloides on feces and enteric methane emissions compare to control.  It concluded that 5% G. procumbens can be used as an anthelmintic forage by improving health status, performance, and reducing methane emissions of sheep.Key words:        Gynura procumbens, herb medicine, nematodes infection, parasite population, sheep performance